2010
DOI: 10.1016/j.crci.2010.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse et propriétés photochimiques de modèles imides et amides contenant des structures norbornadiènes pentaméthylés

Abstract: Me ´moire/Full paper Synthe `se et proprie ´te ´s photochimiques de mode `les imides et amides contenant des structures norbornadie `nes pentame ´thyle ´s Synthesis and photochemical properties of imide and amide models containing pentamethylated norbornadiene residues Ahmed Oueslati a , Hatem Ben Romdhane b, *, Re ´gis Mercier c , Refaa ˆt M. Chaa ˆbouni a a Unite´de recherche synthe`se et analyse de mate´riaux, de´partement de ge´nie industriel, E ´cole nationale d'inge´nieurs de Tunis, BP 37, 1002 Le Belve´… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For the kinetic study, the procedure used for the model compounds and elsewhere published29 was retained. Because the experiences were performed with very thin polymer films, it was assumed that the Beer Lambert's law was applicable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the kinetic study, the procedure used for the model compounds and elsewhere published29 was retained. Because the experiences were performed with very thin polymer films, it was assumed that the Beer Lambert's law was applicable.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work,29 we addressed the synthesis of four pentamethylated NBD models containing imide, bisimide, and diamides moieties and the study of the photochemical isomerization NBD to QC derivatives under solar light irradiations. The results show for all these models that more than 70% of NBD are transformed into QC after only 30 min, and the kinetic reaction is of a first‐order rate.…”
Section: Introductionmentioning
confidence: 99%
“…All solvents were carefully dried and freshly distilled according to common laboratory techniques. 1‐Benzyl‐1,2,3,4,5‐pentamethylcyclopenta‐2,4‐diene and pentamethylated NBD dicarboxylic acid 1 were prepared as previously reported . 4,4′‐Oxydianiline ( 2 , Acros organics, 98%) was purified by vacuum sublimation.…”
Section: Methodsmentioning
confidence: 99%
“…The photoresponsive properties of NBD‐containing polymer materials are usually studied under monochromatic UV irradiation and to the best of our knowledge have never been carried out under sunlight irradiation. We have previously reported the photochemical behavior of NBD‐containing amide and imide models, as well as the photochemical properties of polyimides containing main‐chain pentamethylated NBD moieties obtained by step growth polymerization of a dianhydride pentamethylated NBD with different aromatic diamines . UV/vis spectroscopy of irradiated polymer films has shown that the photochemical isomerization of NBD groups into QC ones proceeds following a first‐order kinetic.…”
Section: Introductionmentioning
confidence: 99%
“…Dicylopentadiene (95%), sodium hydride (60 wt % in paraffin oil), propargyl bromide (80% in toluene), 18‐crown‐6 (99%), potassium carbonate (99%), sodium azide (99.5%), N , N ‐diisopropylethylamine (DIPEA, 99%), 4,4′‐dihydroxybenzophenone (99%), iodo (triethylphosphite) copper(I) (97%), anhydrous tetrahydrofuran (THF, 99.9%), potassium hydroxide (85%), propargyl alcohol (99%), acetylene dicarboxylic acid (95%), but‐2‐yne‐1,4‐diol diacetate (95%), N , N′ ‐dicyclohexylcarbodiimide (99%), 4‐dimethylaminopyridine (DMAP, 99%), and 1,2‐dibromoethane (98%) were purchased from Aldrich and used as received. 2,5‐Norbornadiene‐2,3‐dicarboxylic acid 1 , 2,5‐norbornadiene‐2,3‐dimethylacetate 3 , 2,5‐norbornadiene‐2,3‐diol 4 , and aromatic diazides 6–9 , were prepared according to previously reported methods.…”
Section: Methodsmentioning
confidence: 99%